Strategy for Implementing the KAS-RPA Program (Kampunge Arek Suroboyo Ramah Perempuan dan Anak) Kampung Belajar in Gunung Anyar District - Fisqiyyah Azaliyyah Rahma; Indira Arundinasari (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The Surabaya City Government has implemented the KAS-RPA (Kampung Arek Surabaya Friendly to Women and Children) Program as an effort to achieve equal rights for women and children at the most basic community level. The KAS-RPA program has five indicators in educating them, namely safe villages, foster villages, learning villages, creative-productive villages, and healthy villages. The implementation of the Learning Village in Gunung Anyar Village is one of the efforts to provide equal access and opportunities for women and children to get quality education in the area. This program focuses on non-formal learning assistance activities that involve the active participation of Gunung Anyar Village residents, especially children, as well as handling the problems of children who are indicated as vulnerable to dropping out of school. However, in its implementation there are still some shortcomings. The findings in this study are expected to describe the strategy for implementing the learning village in filling the KAS-RPA Program indicators in Gunung Anyar Village. The research was conducted using a qualitative method, namely through observation and interviews. The purpose of writing this research is to describe the strategies carried out to overcome shortcomings in the implementation of learning village activities to turn on the KAS-RPA Program indicators in Gunung Anyar Village. Keywords: Kampung belajar, Program KAS-RPA